Pola Asuh Orang Tua Tidak Berhubungan dengan Tingkat Kecemasan pada Siswa SMPN Satu Atap Tukdana Indramayu - Isyah; Mia Kusmiati; Elly Marliyani (Bandung Conference Series: Medical Science, 2023)
Abstract. Introduction: Anxiety disorders of adolescents in Indonesia have a prevalence of 65-78% with a percentage in West Java of around 6.5%. Adolescence is a period of transition, a time when individuals are looking for self-identity, and a period of troubled age. Middle school is the right time to represent early adolescence with an age range of 11-17 years. One of the causes of anxiety in adolescents is the authoritarian parenting style. The purpose of this study was to determine the relationship between parenting style and anxiety levels in junior high school students in Indramayu. Methods: This study was conducted in March-July, this study was an observational analytic study with a cross sectional design. The sample in this study used a total sampling of 41 grade 8 students at SMPN 1 TUKDANA ATAP. Measuring tools used are Hamilton Anxiety Rating Scale (HARS) and Parenteral Authority Questionnaire (PAQ) questionnaires. Data analysis used Chi Square test with p-value <0.005. Results: Research shows that parents with democratic parenting style are 61%, authoritarian parenting style is 39%. Most student respondents did not have anxiety, namely 34%, mild anxiety 29%, severe anxiety 22%, and moderate anxiety 14%. The results showed that there was no relationship between parenting style and anxiety level (p-value = 1.000). Discussion: This type of democratic parenting shows responsible attitudes and behavior, accepts criticism openly, is willing to accept, and has stable emotional control so it doesn't cause anxiety in adolescents. Anxiety in adolescents is caused by many factors, such as not being able to adjust to changes, economic problems, physical changes, etc. Abstrak. Pendahuluan: Gangguan kecemasan pada remaja di Indonesia memiliki prevalensi 65-78% dengan jumlah persentase di Jawa Barat sekitar 6,5%. Masa remaja merupakan masa transisi, masa saat individu mencari identitas diri, dan masa usia bermasalah. Masa SMP merupakan masa yang tepat untuk merepresentasikan dari masa remaja awal dengan kisaran usia 11-17 tahun. Salah satu penyebab kecemasan pada remaja adalah pola asuh orang tua dengan tipe otoriter. Tujuan penelitian ini untuk mengetahui hubungan antara pola asuh orang tua dengan tingkat kecemasan pada siswa sekolah menengah pertama di Indramayu. Metode: Penelitian ini dilakukan pada bulan maret-juli, penelitian ini merupakan analitik observasional dengan desain cross sectional. Sampel pada penelitian ini menggunakan total sampling sebanyak 41 orang siswa kelas 8 SMPN 1 ATAP TUKDANA. Alat ukur yang digunakan adalah kuesioner Hamilton Anxiety Rating Scale (HARS) dan Parenteral Authority Questionnaire (PAQ). Analisis data menggunakan uji Chi Square dengan p-value <0,005. Hasil: Penelitian menunjukan bahwa orang tua dengan tipe pola asuh demokratis yaitu 61%, pola asuh otoriter 39%. Responden siswa terbanyak tidak memiliki kecemasan yaitu 34%, kecemasan ringan 29%, kecemasan berat 22%, dan kecemasan sedang 14%. Hasil penelitian menunjukan tidak terdapat hubungan antara pola asuh orang tua dengan tingkat kecemasan (p-value= 1,000). Diskusi: Tipe pola asuh demokratis menunjukan sikap dan perilaku tanggung jawab, menerima kritikan secara terbuka, mau menerima, dan kontrol emosi yang stabil sehingga tidak menimbulkan kecemasan pada remaja. Kecemasan pada remaja disebabkan oleh banyaknya faktor, seperti tidak bisa menyesuaikan diri terhadap perubahan, masalah ekonomi, perubahan fisik, dll.